2003
DOI: 10.1007/s00056-003-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral Comfort, Function and Hygiene in Patients with Lingual Brackets

Abstract: The results of the present study suggest that detailed briefing on the extent and duration of potential impairments in oral comfort, functions and hygiene is advisable prior to the insertion of lingual brackets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
12

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 13 publications
0
22
0
12
Order By: Relevance
“…65% of the patients interviewed by Fritz et al [11] had the greatest problems with this. Hohoff et al [15] found that subjective narrowing of the lingual space did not significantly improve even 3 months after lingual appliance insertion.…”
Section: Beeinträchtigungenmentioning
confidence: 99%
“…65% of the patients interviewed by Fritz et al [11] had the greatest problems with this. Hohoff et al [15] found that subjective narrowing of the lingual space did not significantly improve even 3 months after lingual appliance insertion.…”
Section: Beeinträchtigungenmentioning
confidence: 99%
“…The severity of these problems is commensurate with the thickness of the brackets. 11,13 For 4 years now mini-brackets with a thickness of 1.5 mm have been available on the market. This is the smallest size that can be used, but brackets with a thickness of 2 mm help to reduce discomfort.…”
Section: 13mentioning
confidence: 99%
“…A técnica lingual oferece a opção mais estética de tratamento ortodôntico [2][3][4] , pois os bráquetes ficam invisíveis colados na superfície lingual dos dentes 1,5 e os lábios não ficam protuberantes 5 . Apesar da grande vantagem estética, essa terapia possui também desvantagens, como: restrição no conforto oral 1,[5][6][7][8][9][10][11][12] , na fala 1,[5][6][7][8][9][10][11][12][13][14][15] , na higiene 5,6,8,10,11,14 , pode causar irritações na língua 1,[5][6][7][8][9]11 , restrição no espaço da língua 8 e dificuldades na alimentação [6][7][8]10,11 . Diversos dispositivos linguais têm sido descobertos e clinicamente usados particularmente em pacientes adultos.…”
Section: Descritoresunclassified
“…Assim, diversos autores avaliaram as desvantagens causadas pelos dispositivos linguais verificando que o desconforto 5,6,8,11 , as alterações na fala 5,6,9,11,15 , as lesões na língua 6,11 , uma ligeira perda de paladar no início do tratamento 9 e as dificuldades na alimentação e higienização eram sempre relatados pela maioria dos pacientes 6,8 . Dispositivos linguais de diferentes dimensões vêm sendo testados e embora todos induzam mudanças significativas na cavidade bucal e suas funções, quanto menor for esse dispositivo, menores são as alterações provocadas por eles 12,15 .…”
Section: Revisão Da Literaturaunclassified
See 1 more Smart Citation